Citrus Extract High in Flavonoids Beneficially Alters Intestinal Metabolic Responses in Subjects with Features of Metabolic Syndrome - Maurer Sost, Mônica; Stevens, Yala; Salden, Bouke; Troost, Freddy; Masclee, Ad; Venema, Koen (Foods, 2023)
The objective of this study was to investigate the effects of a citrus extract rich in citrus flavonoids on intestinal metabolic responses in subjects with features of metabolic syndrome, in an in vitro colon fermentation system (TIM-2) and fecal samples obtained from human subjects in an in vivo trial. In the TIM-2 system inoculated with fecal samples of volunteers with features of metabolic syndrome, continuous citrus extract supplementation (500 mg/day) resulted in increased cumulative short-chain fatty acid (SCFA) levels compared to the control condition, which was mainly due to increased production of butyrate, acetate, and valerate. In human volunteers, 12 weeks of daily supplementation with 500 mg citrus extract resulted in a significant shift in the SCFA profile towards more butyrate (p = 0.022) compared to the placebo group. Furthermore, there was a trend towards a reduction in fecal calprotectin levels, a marker for intestinal inflammation, compared to the placebo (p = 0.058). Together, these results suggest that citrus extract intake may have a positive effect on intestinal metabolic responses and through this, on host health in subjects with features of metabolic syndrome. Further research is needed to provide more insight into the potential underlying mechanisms and to study effects on clinical parameters.